2018
DOI: 10.1016/j.diamond.2018.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Multi-walled carbon nanotubes enhanced superhydrophobic MWCNTs-Co/a-C:H carbon-based film for excellent self-cleaning and corrosion resistance

Abstract: A robust superhydrophobic MWCNTs-Co/a-C:H carbon-based film was successfully fabricated for the first time by a safe technology, namely electrochemical deposition. The multi-walled carbon nanotubes (MWCNTs) and Co nano-particles were confirmed to tailor a micro-nanoscale hierarchical surface and nanocrystallite/amorphous microstructure. The resulting WCNTs-Co/a-C:H carbon-based film exhibited complete water repellency with the contact angle (158.1°) and much smaller sliding angle (2.98°), fairly strong mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The anticorrosion performance of the present and previous superhydrophobic surfaces is presented in Table . It could be observed that the present superhydrophobic surface showed larger water contact angle, lower I corr , and larger R p compared to previous works. , , Here, the higher superhydrophobicity and better anticorrosion property were attributed to multiple hybrid structure, as shown in Scheme . First, the thin topcoat consisted of nanoparticles provided superhydrophobicity, resulting from low surface energy and island nanostructure.…”
Section: Resultsmentioning
confidence: 56%
“…The anticorrosion performance of the present and previous superhydrophobic surfaces is presented in Table . It could be observed that the present superhydrophobic surface showed larger water contact angle, lower I corr , and larger R p compared to previous works. , , Here, the higher superhydrophobicity and better anticorrosion property were attributed to multiple hybrid structure, as shown in Scheme . First, the thin topcoat consisted of nanoparticles provided superhydrophobicity, resulting from low surface energy and island nanostructure.…”
Section: Resultsmentioning
confidence: 56%
“…The contact angle of pure Cu foil is approximately 85.2°, whereas the contact angle of the Cu–MoS 2 current collector surface is increased to 135.7° because of the presence of the micro/nanostructure, exhibiting poor wettability. In general, the poorer the wettability of the film, the better the corrosion resistance is, because the film can effectively reduce the contact between the corrosive medium and substrate . Thus, the corrosion medium cannot penetrate into the film .…”
Section: Resultsmentioning
confidence: 99%
“…In general, the poorer the wettability of the film, the better the corrosion resistance is, because the film can effectively reduce the contact between the corrosive medium and substrate. 27 Thus, the corrosion medium cannot penetrate into the film. 28 In other words, the MoS 2 film can effectively slow down the corrosion of the electrolyte to the current collector, increase the stability of the Cu−MoS 2 , and extend the service life of the current collector.…”
Section: Resultsmentioning
confidence: 99%
“…Another experiment [99] was done with silicon wafers coated with a prepared MWCNTs-CO/a-C: by composite electrodeposition method, which obtained WCA to be 158.1˚ and SA to be 2.98˚. In 3.5 wt% of NaCl solution, the coating's anti-corrosion potential reached 98.02%, and excellent wear resistance has proven by the sandpaper wear test.…”
Section: Carbon Nanotube-based Compositementioning
confidence: 99%